2015
DOI: 10.1063/1.4906593
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide overprints for flexible and transparent electronics

Abstract: The overprints produced in inkjet technology with graphene oxide dispersion are presented. The graphene oxide ink is developed to be fully compatible with standard industrial printers and polyester substrates. Post-printing chemical reduction procedure is proposed, which leads to the restoration of electrical conductivity without destroying the substrate. The presented results show the outstanding potential of graphene oxide for rapid and cost efficient commercial implementation to production of flexible elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…To address this limitation, alternative methods such as laser annealing, chemical reduction, and intensive light reduction have been developed. While effective at addressing the substrate temperature issue, chemical reduction uses toxic or acidic chemicals such as hydrazine, hydrobromic acid, and hydroiodic acid, and the reduction process can only be performed on chemically‐inert, nonabsorbent materials. Laser and intensive light methods use focused light for localized annealing, but to minimize thermal damage to the substrate, the substrate material should either be transparent to the incident light, the exposure period must be precisely managed to prevent overheating, or the light source should be controlled to illuminate only the printed structure .…”
Section: Introductionmentioning
confidence: 99%
“…To address this limitation, alternative methods such as laser annealing, chemical reduction, and intensive light reduction have been developed. While effective at addressing the substrate temperature issue, chemical reduction uses toxic or acidic chemicals such as hydrazine, hydrobromic acid, and hydroiodic acid, and the reduction process can only be performed on chemically‐inert, nonabsorbent materials. Laser and intensive light methods use focused light for localized annealing, but to minimize thermal damage to the substrate, the substrate material should either be transparent to the incident light, the exposure period must be precisely managed to prevent overheating, or the light source should be controlled to illuminate only the printed structure .…”
Section: Introductionmentioning
confidence: 99%
“…21 The GO thin films of various thicknesses (continuously changing between edge and center of the sample in the range of 20-100 nm) were obtained by spin-coating water solution of GO on a 40 nm thick Pt film on Si substrate. Standard Pt covered LC-AFM tips served both for imaging and as a top electrode.…”
mentioning
confidence: 99%
“…Moreover, a decrease of concentration of functionalities is observed, which is an indication of reduction GO to rGO. 21 Observed transition between OFF and ON states is a signature of the RS process occurring in GO layers. In order to determine what are the main factors influencing the RS process, we decided to investigate its efficiency (diameter d of ON region created after PM) as a function of atmosphere composition.…”
mentioning
confidence: 99%
“…[12,[14][15][16][17][18] Generally, 2D material inks show similar drying behavior to inks made from nanoparticles or nanotubes, i.e. under appropriate drying conditions they show a clear coffee ring with the 2D flakes or 1D tubes arranged at the contact line forming a characteristic ringlike structure.…”
mentioning
confidence: 99%
“…under appropriate drying conditions they show a clear coffee ring with the 2D flakes or 1D tubes arranged at the contact line forming a characteristic ringlike structure. [14,15] Ring formation can be suppressed, for example, by using two solvents [16,17] or adding surfactant and a high boiling point solvent. Recent work by Kim et al identified both an effect of size and an effect of temperature on the transition to a coffee ring during the drying of suspensions of graphene oxide (GO), [19] with higher drying temperatures suppressing coffee ring formation and a slightly lower critical temperature for ring suppression with inks containing larger GO flakes.…”
mentioning
confidence: 99%